Relationship between growth hormone-releasing hormone and somatostatin in the rat: effects of age and sex on content and in-vitro release from hypothalamic explants. - Ge, F; Tsagarakis, S; Rees, L; Besser, G; Grossman, A (1989)
Secretion of GH in the rat has been shown to be dependent upon age and sex. Using rat hypothalamic explants in vitro, we have studied the release and hypothalamic content of GH-releasing hormone (GHRH) and somatostatin in male and female Wistar rats at four different ages (10, 30 and 75 days, and 14 months). Basal release of GHRH was not significantly different between male and female rats, but at all ages males released more GHRH in response to stimulation by both 28 and 56 mmol potassium/l than female rats (P less than 0.05). Neither basal nor potassium-stimulated release of GHRH altered with age. In contrast, both basal and potassium-stimulated secretion of somatostatin increased significantly (P less than 0.01) with age, but was the same in the two sexes. Hypothalamic GHRH content, as assessed by the extractable tissue content following incubation, was significantly (P less than 0.01) lower in 10-day-old rats compared with older rats, but remained constant after 30 days of age. Somatostatin content, in contrast, increased progressively with age (P less than 0.01). The hypothalamic content of the two peptides was the same in both sexes. In conclusion, our findings demonstrate that male rats release more GHRH in vitro than female rats, possibly reflecting the increased pulse amplitude of GH seen in males in vivo; the progressive fall in secretion of GH previously reported during ageing appears to parallel the progressive increase in somatostatin release and content seen in our in-vitro system.